Challenges of Managerial Functions Emerging within IGRA Professional Organizations in East Kalimantan - Rukiyah, Ity; Kadir, Marniati; Ulfah, Zakiyah (IAIN Samarinda, 2021)
The function of Ikatan Guru Raudhatul Athfal, or what so-called by IGRA is ideally as a forum for professional development of educators and educational members of Early Childhood Education or ECE institutions. This research is aimed to figure out challenges faced by IGRA in East Kalimantan in relation to principles of organizational management i.e, planning, organizing, actuating, and controlling, or what so-called by POAC. In-dept interview was done to the head and members of IGRA in East Kalimantan in four different cities i.e, Samarinda, Balikpapan, Tenggarong, and Berau. Findings of this research indicate that principles of organizational management have not effectively been employed due to very crucial challenges, including leadership, organizational funding, IGRA members competency, government support, and some other critical barriers that trigger insufficient management implementation of IGRA in East Kalimantan. Research implications and suggestions are discussed further in this research.Â Â